Fixation of intra-articular calcaneal fractures: A comparative study of the postoperative outcome between HA/PPLA screws and locking plates. Issue 3 (March 2023) - Usami, Takuya; Takada, Naoya; Nishida, Kazuki; Sakai, Hiroaki; Iwata, Hidetoshi; Yonezu, Hiroki; Sekiya, Isato; Nagaya, Yuko; Ueki, Yoshino; Murakami, Hideki; Kuroyanagi, Gen
Abstract: Background: Forged unsintered hydroxyapatite and poly l -lactic acid ( F-u-HA/PLLA) screw is bioactivite, bioabsorbable, and radiopaque with high mechanical strength. Its efficacy has been previously demonstrated in the treatment of lateral humeral condylar, lateral tibial condylar, ankle, and patellar fractures. However, studies on its efficacy in treatment of calcaneal fractures is lacking. This study aimed to compare the postoperative results of F-u-HA/PLLA screw fixation and locking plate fixation for intra-articular calcaneal fractures. Methods: From January 2013 to December 2019, 47 closed intra-articular fractures treated with either F-u-HA/PLLA screws (group S, 18 feet in 17 patients) or locking plates (group P, 29 feet in 28 patients) in a single trauma center were retrospectively reviewed. The sinus tarsi approach was used in both groups. The time to bone union, step-off, varus deformity, Bohler's angle, and width and height of the calcaneus were assessed after surgery. Ankle joint range of motion (ROM) and postoperative complications were also assessed. Results: All fractures were successfully treated. The Kaplan-Meier curves of the two groups showed similar trends. The log-rank test showed no significant difference in the time to bone union between the two groups (p = 0.48). In the Cox proportional hazards model adjusted for preoperative width and Bohler's angle, the hazard ratio for bone union was not statistically significant (HR: 1.13, 95%CI: 0.50–2.56, p = 0.78). Other variables included step-off (group S: 2.0 vs group P: 2.2 mm, p = 0.84), varus deformity (2.0° vs. 3.0°, p = 0.7), Gissane's angle (103.5° vs 104.0°, p = 0.84), width (38.0 vs 34.8 mm, p = 0.12), height (42.1 vs 44.0 mm, p = 0.07), and ankle ROM degrees (dorsal flexion, 20.0° vs. 20.0°, p = 0.13; plantar flexion 40.0° vs 40.0°, p = 0.56), which were not significantly different between groups P and S. The Bohler's angle was smaller in group S than in group P (20.5° vs 27.0°, p < 0.01). No skin necrosis or infection was observed in either group. Conclusion: Postoperative results of F-u-HA/PLLA screw fixation using the sinus tarsi approach for intra-articular calcaneal fractures were as good as those of locking plate fixation. Highlights: F-u-HA/PLLA screws have properties of bioactivity and bioabsorbability with high mechanical strength. Postoperative and radiographic outcomes of F-u-HA/PLLA screw and plate fixation for calcaneal fractures were evaluated. F-u-HA/PLLA screw fixation for calcaneal fractures provides similar postoperative outcomes than locking plate fixation.